PENATAAN RUANG PERKOTAAN YANG BERKELANJUTAN, BERDAYA SAING DAN BEROTONOMI (Suatu Tinjauan Pustaka) - Suweda, I Wayan (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 2 Juli 2011, 2012)
"The development that we do need to realize is that future generations will be able to enjoy what we feel at this moment ...". This means that the progress resulting from the interaction of environmental aspects, the economic dimension and socio-political aspects in such a way is to guarantee each human life that live in the present and future and is accessible to socio-economic development without exceeding environmental limits. Urban development should promote a sense of justice, and sustainable local economy by increasing the presence of the informal sector as social nets, and the preservation of the heritage area to provide a collective memory for the community. Thus, the creation of sustainable city, competitive and autonomous through the planning and management will be effective only if integrated with land use management strategies and the environment.
Keywords: sustainable development, urban area, planning